Performance of a geosynthetic-encased column (GEC) in soft ground: numerical and analytical studies. Issue 4 (August 2013) - Almeida, M.S.S.; Hosseinpour, I.; Riccio, M.
Abstract : ABSTRACT: Stone columns with granular material are often used to support embankments over soft soil. In extremely soft soils, encasing the granular column with geosynthetic material improves their stiffness and strength. Based on the soil and column properties, settlements and stresses can be determined by means of analytical solutions or numerical analyses, and this paper compares the results of these two procedures by means of parametric analyses. Two-dimensional finite-element analysis (FEA) was used to simulate the behavior of a geosynthetic-encased stone column in soft clay loaded by an embankment. Parametric studies are then carried out by varying the thickness of the soft soil layer and the tensile stiffness of the geosynthetic encasement for a given set of soft clay and column parameters. The results of FEA have shown that the influence of the geosynthetic encasement on settlement improvement increases in shallow soft soil layers. It was also observed that the dependence of stress concentration on the thickness of the soft soil increases with geosynthetic stiffness. The critical embankment height where ground settlement is negligible was also investigated.